Effect of occupational stress on depression and sleep of gene sequencing enterprise employees - Ming XU; Tenglong YAN; Tingting XIE; Huining WANG; Xiaowen DING; Dongsheng NIU (环境与职业医学, 2022)
BackgroundGene sequencing industry is an emerging innovation-driven industry. Employees have high requirements for independent learning and innovation ability and face great professional pressure. ObjectiveTo understand the occupational stress, depression, and sleep of gene sequencing enterprise employees and to analyze the effect of occupational stress on depression and sleep. MethodsFrom November to December 2021, occupational stress, depression, and sleep conditions of 469 workers from 34 enterprises in gene sequencing industry were surveyed by Core Occupational Stress Scale (COSS), Patient Health Questionnaire 9 (PHQ-9), and Pittsburgh Sleep Quality Index (PSQI). A total of 427 valid questionnaires were recovered with a questionnaire valid response rate of 91.04%. The relationship of occupational stress with depression or sleep was analyzed by logistic regression. ResultsThe rates of occupational stress, depression, and sleep disorder were 27.40%, 33.50%, and 28.10%, respectively. Significant difference were found in the rates of depression and sleep disorder in different occupational stress groups (P<0.05). The results of logistic regression analysis showed that, for every 1 increase in social support score, the risk of depression increased by 1.206 (95%CI: 1.117−1.304), and the risk of sleep disorder increased by 1.143 (95%CI: 1.059−1.233). For every 1 increase in organization and reward score, the risk of developing depression increased by 1.082 (95%CI: 1.017−1.151). Mild, moderate, and severe occupational stress were all associated with a higher risk of depression in reference to no occupational stress (OR=2.535, 95%CI: 1.465−4.386; OR=3.774, 95%CI: 1.809−7.870; OR=3.823, 95%CI: 1.486−9.837). Severe occupational stress was associated with a higher risk of sleep disorder in reference to no occupational stress (OR=3.141, 95%CI: 1.233−8.006). ConclusionOccupational stress among employees in the gene sequencing industry can increase the risks of depression and sleep disorder. Enterprises need to take intervention measures and pay attention to prevention and treatment.